Accuracy of arterial [18F]-Fluorodeoxyglucose uptake quantification: A kinetic modeling study - Toczek, Jakub; Wu, Jing; Hillmer, Ansel T.; Han, Jinah; Esterlis, Irina; Cosgrove, Kelly P.; Liu, Chi; Sadeghi, Mehran M. (Journal of nuclear cardiology, 2020)
2-deoxy-2- [18F] fluoro-d-glucose (FDG) PET is commonly used for the assessment of vessel wall inflammation. Guidelines for analysis of arterial wall FDG signal recommend the use of the average of maximal standardized uptake value (mean SUVmax) and target-to-blood (mean TBRmax) ratio. However, these methods have not been validated against a gold standard such as tissue activity ex vivo or net uptake rate of FDG (Ki) obtained using kinetic modeling. We sought to evaluate the accuracy of mean SUVmax and mean TBRmax for aortic wall FDG signal quantification in comparison with the net uptake rate of FDG. Dynamic PET data from 13 subjects without prior history of cardiovascular disease who enrolled in a study of vascular inflammation were used for this analysis. Ex vivo measurement of plasma activity was used as the input function and voxel-by-voxel Patlak analysis was performed with t* = 20 minute to obtain the Ki image. The FDG signal in the ascending aortic wall was quantified on PET images following recent guidelines for vascular imaging to determine mean SUVmax and mean TBRmax. The Ki in the ascending aortic wall did not correlate with mean SUVmax (r = 0.10, P = NS), but correlated with mean TBRmax (r = 0.82, P < 0.001) (Figure 1B). Ki and Ki_max strongly correlated (R = 0.96, P < 0.0001) and similar to Ki, Ki_max did not correlate with mean SUVmax (r = 0.17, P = NS), but correlated with mean TBRmax (r = 0.83, P < 0.001). Kinetic modeling supports the use of mean TBRmax as a surrogate for the net uptake rate of FDG in the arterial wall. These results are relevant to any PET imaging agent, regardless of the biological significance of the tracer uptake in the vessel wall.